"Pitfalls" of infants' immune systems and nutritional problems: what is the relationship? Questions and answers - M. S. Savenkova (Лечащий Врач, 2024)
Introduction. Based on the peculiarities of the formation of the child's immune system, pediatricians are particularly concerned about infants, who have a tendency to generalization of infectious processes (viral and bacterial) and are characterized by physiological deficiency of immunoglobulin A, frequent diseases of the respiratory and intestinal tract, and the development of dysbiosis of mucous membranes. The organization of proper adapted nutrition of children is of great importance for their growth and development. It is not only about pathology, but also various functional disorders of the gastrointestinal tract, which can arise and a healthy baby as a result of improper nutrition or introduction of complementary foods. For infants of the first months of life, the gold standard of nutrition is breast milk of the mother, and if breastfeeding is impossible – an adapted milk formula. Early introduction of complementary foods is inappropriate, as the body of an infant under 4-6 months is not yet ready to accept other foods. However, in conditions of deficiency of breast milk or in its absence, it is necessary to choose its substitute. In this situation, infant adapted formulae based on natural goat's milk are recommended.Objective. The article presents the peculiarities of the immune system of young children and critical periods of its development. It shows the relationship between the development of diseases, immune system and the possibility of correction with the help of proper nutrition and complementary feeding.